The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1086/653677
|View full text |Cite
|
Sign up to set email alerts
|

Infrequent Recovery of HIV from but Robust Exogenous Infection of Activated CD4+T Cells in HIV Elite Controllers

Abstract: HIV elite controllers are able to control HIV-1 infection spontaneously to undetectable levels in the absence of antiretroviral therapy, but the mechanisms leading to this phenotype are poorly understood. Although, low frequencies of HIV infected peripheral CD4+ T-cells have been reported in this group, it remains unclear to what extent this is due to viral attenuation, active immune containment, or intracellular host factors that restrict virus replication. Here we assessed proviral DNA levels, autologous vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
98
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 28 publications
20
98
1
Order By: Relevance
“…Several prior studies have demonstrated that CD4 + T cells from elite controllers are generally permissive to HIV-1 infection and that they can harbor pathogenic, replication-competent virus in vivo (12)(13)(14). Moreover, after in vitro activation, CD4 + T cells from elite controllers are capable of supporting productive HIV-1 infection (13,15), but prior experimental procedures, particularly when involving vigorous in vitro activation of cells, may have been insufficiently sensitive to detect intrinsic resistance mechanisms that restrict HIV-1 replication by altered expression patterns of host genes.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies have demonstrated that CD4 + T cells from elite controllers are generally permissive to HIV-1 infection and that they can harbor pathogenic, replication-competent virus in vivo (12)(13)(14). Moreover, after in vitro activation, CD4 + T cells from elite controllers are capable of supporting productive HIV-1 infection (13,15), but prior experimental procedures, particularly when involving vigorous in vitro activation of cells, may have been insufficiently sensitive to detect intrinsic resistance mechanisms that restrict HIV-1 replication by altered expression patterns of host genes.…”
Section: Introductionmentioning
confidence: 99%
“…One study suggested that cells from ES were resistant to infection because of selective up-regulation of cyclin-dependent kinase inhibitor p21 (31), whereas another study also found resistance of ES CD4 + T cells to HIV-1 infection but showed that p21 plays no role in this phenomenon (32). A third study found that CD4 + T cells from ES were as susceptible to infection as CD4 + T cells from HIV-1 seronegative donors (9). Because activation by either method, PHA or anti-CD3 antibodies, has been shown to modulate coreceptor density, which, in turn, affects susceptibility to infection (33)(34)(35), we have studied the susceptibility of unstimulated CD4 + T cells.…”
mentioning
confidence: 99%
“…Quantitative PCR (qPCR) was performed using long terminal repeat (LTR) primers to determine the frequency of proviral HIV-1 DNA in circulating CD4 ϩ T cells and monocytes. Single-step qPCR was performed on each sample under previously published conditions (29). The proviral HIV-1 DNA copy number was calculated relative to the RNase P gene copy number (Applied Biosystems), which had been previously quantified with a standard curve.…”
mentioning
confidence: 99%